Leadership style for Thailand 4.0 of school administrators affecting the implementation of the educational quality assurance system of schools at the secondary education level within the jurisdiction of Bangkok under a new educational quality assurance fr (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aimed to 1) study and compare the leadership styles for Thailand 4.0 among school administratorsclassified by school status and size within the jurisdiction of Bangkok 2) study and compare operations in the educational qualityassurance system of secondary schools within the jurisdiction of Bangkok under the new educational quality assuranceframework classified by school status and size and 3) study the predictive power of the leadership style for Thailand 4.0 of schooladministrators impacting the implementation of the education quality assurance system under the new education qualityassurance framework, classified by school status and size within the jurisdiction of Bangkok affecting the implementation of theeducational quality assurance system of schools within the jurisdiction of Bangkok. The sample was 201 school administratorsand teachers. The research instruments were questionnaires. The research found that the leadership style for Thailand 4.0 withinthe jurisdiction of Bangkok of school administrators was at high level. The comparative results classified by overall status showedthat there was a statistically significant difference in style at .01 levels. When compared from the overall school size classificationwithin the jurisdiction of Bangkok, there was a statistically significant difference in style at the .05 level (2). The implementationof the educational quality assurance system at secondary schools within the jurisdiction of Bangkok under the new educationalquality assurance framework was at high level. The comparative results classified by overall status showed that there was astatistically significant difference in style at .01 levels. When compared by size of schools within the jurisdiction of Bangkok,there was a statistically significant difference at .05 levels (3). The results of a predictive power analysis of leadership style forThailand 4.0 among school administrators found that there were five components capable of forecasting operations in theeducation quality assurance system under the new framework for quality assurance for secondary schools within the jurisdictionof Bangkok under the new educational quality assurance framework, at 89% considere